Diagnostics of glaucoma before clinical manifestations - N.E. Fomin; A.V. Kuroyedov (РМЖ "Клиническая офтальмология")
Diagnostics of glaucoma before clinical manifestations N.E. Fomin1,2, A.V. Kuroyedov1,2 1P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation The aim of current diagnostics of primary open-angle glaucoma (POAG) is to detect clinical manifestations of the disease. However, a set of preclinical diagnostic techniques to discover POAG predictors before typical signs occur are more promising. Among these methods is DNA testing, e.g., the identification of genetic mitochondrial dysfunction (mitochondria are the major producer of cellular energy). Evaluation of biochemical markers in body fluids (i.e., aqueous humor, blood, tears) may provide insight into the course of POAG but also early detection of glaucoma risk factors. Instrumental tests are of particular importance as they help assess morphological and functional changes in various ocular tissues. “General” instrumental tests are Doppler sonography of the head and neck, magnetic resonance imaging, and cerebrospinal fluid pressure measurement. “Topical” instrumental tests are retinal vascular assessment, identification of apoptotic cells, and electroretinography. Detailed evaluation of ganglion cells and verification of their changes are one the promising area. This will help reach a new level of POAG diagnostics, prevent advanced disease, and significantly improve the quality of life. Keywords: glaucoma, primary open-angle glaucoma, diagnostics of glaucoma, preclini cal diagnostics, intraocular pressure, markers, apoptosis. For citation: Fomin N.E., Kuroyedov A.V. Diagnostics of glaucoma before clinical manifestations. Russian Journal of Clinical Ophthalmology. 2020;20(3):152–158. DOI: 10.32364/2311-7729-2020-20-3-152-158.